The psycho-lexical structure of sports culture - Guo, Yuanbing; Ye, Na; Hong, Xiaobin; Wang, Wenjing (Frontiers in Psychology, 2022)
The psycho-lexical approach can be effectively used to explore the structure of sports culture. Based on a lexical list of adjective vocabulary reflecting sports culture and through an item analysis, 87 discriminating objectives were selected representing sports culture.Objective: to explore the structure of sports culture from the objectives lexicons. Methods: Item analysis and factor analysis were adopted to abstract the structure of sports culture. Results: Through a principal component analysis, a structure of six factors including extroversion-activity, diligence-progression, experience, independence-excellence, enjoyment, and body culture was extracted. Through a second-order factor analysis, a psychological structure of sports culture consisting of six dimensions and 12 factors was extracted, and result of the reliability analysis revealed good Cronbach α coefficient and test-retest reliability coefficient. Conclusions: The psycho-lexical structure of sports culture can be used to understand structure of sports culture.